The Protestant Enlightenment Revisited: Daniel Coit Gilman and the Academic Reforms of the Modern American University - Hart, D. G. (The journal of ecclesiastical history, 1996)
An exchange took place at the end of the nineteenth century between William Rainey Harper and Dwight L. Moody that makes little sense to those who study American intellectual life at the end of the twentieth. What is remarkable about this incident is not that Harper, the president of the University of Chicago, a new institution dedicated to promoting science, advanced research and graduate education, invited Moody, the leading revivalist of the Gilded Age, to speak at one of America's most promising new universities. To be sure, our understanding of the educational reforms associated with the founding of research universities rarely encompasses the transatlantic revivals of Moody and his song leader, Ira Sankey. And Harper's invitation to Moody could reasonably be compared to the contemporary practice of conferring honorary degrees on civic leaders and celebrities not known for their interest in higher education but whose reputation could well benefit the degree-granting institution. What is exceptional in this exchange is Harper's assessment of the similarities between his university and Moody's revivals. While Harper acknowledged the use of different means, he thought his and Moody's aims were the same. ‘I do not understand’, Harper wrote, ‘that you, as a matter of fact, represent any other position than that which is actually maintained here at the University. The differences between us are merely differences of detail.’